Oscillation of certain fourth-order functional differential equations - Agarwal, P.; Grace, S. R.; O’Regan, D. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Some new criteria for the oscillation of fourth-order nonlinear functional differential equations of the form d^2dt^2 (a(t) (d^2x(t)dt^2)^α ) + q(t)f(x[g(t)])=0, α>0, are established.